2015
DOI: 10.1128/aem.03269-14
|View full text |Cite
|
Sign up to set email alerts
|

Large Fractions of CO 2 -Fixing Microorganisms in Pristine Limestone Aquifers Appear To Be Involved in the Oxidation of Reduced Sulfur and Nitrogen Compounds

Abstract: The traditional view of the dependency of subsurface environments on surface-derived allochthonous carbon inputs is challenged by increasing evidence for the role of lithoautotrophy in aquifer carbon flow. We linked information on autotrophy (Calvin-Benson-Bassham cycle) with that from total microbial community analysis in groundwater at two superimposed-upper and lower-limestone groundwater reservoirs (aquifers). Quantitative PCR revealed that up to 17% of the microbial population had the genetic potential to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 77 publications
6
91
0
Order By: Relevance
“…Within the time period of monitoring there was no significant change from previous reported hydrochemical patterns (Table 1) (Herrmann et al, 2015;Küsel et al, 2016). Water chemistry reflects the limestone environment of the catchment.…”
Section: Hydrochemistrymentioning
confidence: 73%
See 2 more Smart Citations
“…Within the time period of monitoring there was no significant change from previous reported hydrochemical patterns (Table 1) (Herrmann et al, 2015;Küsel et al, 2016). Water chemistry reflects the limestone environment of the catchment.…”
Section: Hydrochemistrymentioning
confidence: 73%
“…Chemolithoautotrophic microorganisms, i.e., microbes that metabolize CO 2 instead of organic carbon, have been shown to be key players and important primary producers in groundwater microbial communities (Alfreider et al, 2012;Hutchins et al, 2016;Kellermann et al, 2012). A high potential for microbial CO 2 fixation has already been demonstrated in our studied aquifers by molecular analyses (Herrmann et al, 2015;Lazar et al, 2016a;Schwab et al, 2017b). We hypothesized that turnover of OM derived from chemoautotrophic microorganisms should be reflected in DIC isotopes, since OM derived from CO 2 fixation should be isotopically distinct from other sources like surface-derived OM or sedimentary organic matter.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Initial investigations have identified two factors which appear to be key drivers of microbial community composition and thus also strongly influence the potential for biogeochemical processes to take place: (i) the strong differences in oxygen availability between the two aquifers, and (ii) the distance to surface soils and thus the likelihood of the input and potential establishment of soil-derived microbial groups in the aquifer microbial communities (Opitz et al, 2014;Herrmann et al, 2015). Comparative investigations of microbial community structure in the groundwater using next generation amplicon sequencing of 16S rRNA genes and transcripts revealed that members of the Betaproteobacteria and the CytophagalesFlavobacteria-Bacteroidetes group dominate in the upper, anoxic aquifer while members of the Deltaproteobacteria and Nitrospira dominate the communities in the oxic, lower aquifer .…”
Section: Microbial Communitiesmentioning
confidence: 99%
“…The type strain of Sulfuricella denitrificans was isolated from a cold anoxic hypolimnion of a freshwater lake, and was characterized as a psychrotolerant sulfur oxidizer (Watanabe et al, 2012). Based on nucleotide sequences, its close relatives have been found in freshwater lake sediments (Nelson et al, 2007;Song et al, 2012;Watanabe et al, 2013), Thioploca samples from two freshwater lakes (Nemoto et al, 2011), drinking water distribution systems (Li et al, 2010;Sun et al, 2014a, b), the sediment of a drinking water reservoir (Cheng et al, 2014), soil (Field et al, 2010), a bioreactor (Wang et al, 2015), subglacial sediment (Boyd et al, 2014), wetland sediment (Liu et al, 2014), a limestone aquifer (Herrmann et al, 2015), groundwater (Hong et al, 2013), black shale (Li et al, 2014), a horizontal subsurface flow system constructed in wetlands (Zhong et al, 2015) and the freshwater layer of a meromictic lake (Kubo et al, 2014). Members of the genus Sulfuricella are likely to contribute to sulfur cycling in a wide range of freshwater ecosystems, but only two cultured strains of the genus Sulfuricella have, so far, been described (Watanabe et al, 2015b).…”
mentioning
confidence: 99%